Diversity of fungi associated with petroglyph sites in the Negev Desert, Israel, and their potential role in bioweathering - Rabbachin, Laura; Nir, Irit; Waldherr, Monika; Vassallo, Ylenia; Piñar, Guadalupe; Graf, Alexandra; Kushmaro, Ariel; Sterflinger, Katja (Frontiers in Fungal Biology, 2024)
The petroglyphs of the Negev desert, Israel, are a famous and valuable archaeological remain. Previous studies have investigated the microbial communities associated with petroglyphs and their potential role in stone deterioration, nevertheless the role of fungi remains unclear. In this study, the fungal communities present on the stone and, as a comparison, in the surrounding environment (soil and air) at Negev petroglyph sites were analyzed by means of culture-dependent and -independent (metagenomic) techniques. The metagenomic results showed a high fungal biodiversity in the soil, and both approaches highlighted the prevalence of species producing melanized, large, thick-walled spores (mainly Alternaria spp.). From the air sampling, instead, mostly Cladosporium spp. were retrieved. On the other hand, on the rock, the results seem to indicate a low presence of fungi, but with a rock-specialized mycobiota, consisting of extremotolerant microcolonial fungi (MCF) (e.g. Vermiconidia, Coniosporium) and lichens (Flavoplaca). In addition, low proportions of cosmopolitan fungi were detected on the stone, but the comparison of the data clearly indicates that they are transients from surrounding environment. The ability of the isolated strains to dissolve CaCO3, and therefore be a potential threat to the petroglyphs (limestone substrate) was tested, but only one strain resulted positive to acid production under laboratory conditions. Nevertheless, both lichens as well as MCF detected in this study are well-known stone deteriogens, thus may have a significant impact on the petroglyphs deterioration.